(2E)-3-Phenylprop-2-en-1-yl thiocyanate - Ezzat Khan; Adnan Shahzad; M. Nawaz Tahir; Muhammad Ateeq (IUCrData, 2017)
In the title compound, C10H9NS, the C—S—C bond angle is 99.41 (9)° and the dihedral angle between the trans-alkene fragment and the benzene ring is 16.49 (19)°. In the crystal, inversion dimers linked by pairs of extremely weak C—H...N interactions occur, as does a short S...N contact [3.2258 (19) Å].